PERLINDUNGAN HUKUM BAGI KONSUMEN YANG BELUM CAKAP TERHADAP PLAY MUSIC DALAM BENTUK VIDEO KLIP DEWASA - Faradella Syafitri; H.R.Adianto Mardijono (Gapenas Publisher, 2022)
Pornography is a bad intake for children's development, especially in video clips consumed by children as a form of sexual exploitation, so that protection of children needs sufficient attention. Allowing children to access sites that contain pornography will have a major impact on the child's development process. The purpose of this study is to find out what forms of legal protection are applied to children who consume sites that contain pornography. The research method uses normative research methods. The technical analysis of legal materials in this study uses qualitative analysis. Based on the results of the study, the form of legal protection for children who use pornography is to provide a sense of security, security and welfare for the child by providing special protection to children so that bad habits and mental health are not disturbed. Protect children who value pornography over rehabilitation . Efforts that can be made by parents as the closest people, government and society to prevent the occurrence of bad habits committed by children who consume pornography, namely as parents are obliged to give directions to children which actions are not allowed which are not permitted, often taking children to go recite the Koran so that the child can be busy with good things, hold seminars, appeals or socialization to the community so that the protection of children from cases related to pornographic sites is not spread to the younger generation for the nation's successors and can be done by various means of prevention